Advanced engineering technology III selected, peer reviewed papers from the 2nd International Conference on Advanced Engineering and Technology (ICAET 2015) December 11-13, 2015, Incheon, South Korea - Hu, Jong Wan; Kim, Sung Whan (Applied mechanics and materials, 2017)
Selected, peer reviewed papers from the 2nd International Conference on Advanced Engineering and Technology (ICAET 2015) December 11-13, 2015, Incheon, South Korea